2018
DOI: 10.7754/clin.lab.2017.170827
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of MicroRNA-18a for Gastric Cancer: a Meta-Analysis

Abstract: miR-18a could be a promising noninvasive biomarker in gastric carcinoma diagnosis. Further prospective studies should be conducted to highlight the theoretical strengths before its use in clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Increased circulating miR-18a may also be a prognostic factor for lung cancer (18). A meta-analysis revealed that miR-18a may be a promising biomarker for the diagnosis of patients with gastric carcinoma (19). The results obtained in the current study are in accordance with the aforementioned studies.…”
Section: Discussionsupporting
confidence: 90%
“…Increased circulating miR-18a may also be a prognostic factor for lung cancer (18). A meta-analysis revealed that miR-18a may be a promising biomarker for the diagnosis of patients with gastric carcinoma (19). The results obtained in the current study are in accordance with the aforementioned studies.…”
Section: Discussionsupporting
confidence: 90%